2010
DOI: 10.1007/128_2010_64
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbranched Polyamines for Transfection

Abstract: The successful application of gene therapy through DNA transfection into the cell is still a great challenge in ongoing research. Hyperbranched polyamines are highly branched macromolecules, and have gained significant attention in the last two decades, due to their relative ease of preparation, their shape, and their multi-functionality.This review deals with the syntheses of various hyperbranched polyamines that are prepared through a one-step polymerization process. Furthermore, we present the current statu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 141 publications
1
35
0
Order By: Relevance
“…[120] Hyperbranched polymers are highly branched molecules composed of dendritic (D), linear (L), and terminal units (T) that represent a compromise between the perfect structures of dendrimers and the partially degraded architectures. [24] Instead of the tedious step-wise synthesis of perfect dendrimers, hyperbranched polymers are prepared in a one-step synthetic strategy. [188] Due to their similar physicochemical Germany) as in vitro transfections agents.…”
Section: Cationic Polymersmentioning
confidence: 99%
See 2 more Smart Citations
“…[120] Hyperbranched polymers are highly branched molecules composed of dendritic (D), linear (L), and terminal units (T) that represent a compromise between the perfect structures of dendrimers and the partially degraded architectures. [24] Instead of the tedious step-wise synthesis of perfect dendrimers, hyperbranched polymers are prepared in a one-step synthetic strategy. [188] Due to their similar physicochemical Germany) as in vitro transfections agents.…”
Section: Cationic Polymersmentioning
confidence: 99%
“…[22][23] The successful application of gene therapy is still a great challenge in ongoing research, since the most difficult obstacles to overcome have been the inability to transfer the 1 Introduction appropriate gene to a target, prolonged gene expression, and to obtain low toxicity. [24][25] Gene transfer of a nucleic acid to somatic cells can take place either in vivo or ex vivo and the process by which genes are transferred into cultured mammalian cells is called transfection. [26] In vivo therapy is accomplished by transfer of genetic materials directly to the patient, whereas in the ex vivo approach, the therapeutic genes are removed from the patient"s body, genetically modified in vitro, and finally retransplanted (Figure 3).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This has already shown advantageous properties, for instance, in gene delivery applications. 10 Copyright: American Scientific Publishers widened the possibility for cellular and tissue targetability because they allow an increase of the particle dimensions to more than 10 nm, the size limit presently achievable by perfect dendrimers. The great versatility of the dendritic polymers synthesis allows to fine tune physico-chemical parameters such as particle size, water solubility, surface charge, flexibility, branching density, chemical functionality, etc., which are relevant for the successful preparation of drug delivery systems.…”
Section: Introductionmentioning
confidence: 99%
“…Among such potential molecules, those which can further compact DNA molecules into nanosized particles following molecular recognition can aid transport of DNA into the cells. [1,2] Molecular recognition of the nucleotides by natural polyamines, [3,4] synthetic macrocyclic polyamine receptors, [5][6][7][8][9] polyamine polymers [10,11] and dendrimers [12,13] has been demonstrated. It was shown that the efficiency of the cell transfection and cytotoxicity positively correlate with the ratio of amino groups in receptor molecule to the number of phosphate groups in the DNA molecule (N/P).…”
Section: Introductionmentioning
confidence: 99%